Contraintes organisationnelles et gestion des risques en milieu ouvert : l’activité des monteurs installateurs de structures de fête - Valérie Zara-Meylan (Perspectives Interdisciplinaires sur le Travail et la Santé)
In this article, we analyze the work activity of festival equipment erectors and installers in a large city local authority. The purpose is to identify, in this type of open system, the organizational constraints caused by the many decision levels and networks of actors with their own specific objectives. These constraints have a cost for the operators, especially in terms of occupational risks.After showing the limitations of " vertical " risk management, the individual and collective regulations that are implemented in the teams in order to manage the risks are analyzed from the standpoint of the articulation of older workers’ and novices’ roles in the action process, in several situations.The methodology associates in situ analysis, questionnaires and trend charts, and is used to identify critical situations that occur when multiple actors intervene upstream from and on the sites. These actors disrupt the " horizontal " risk management provided by the older workers, who are forced to make compromises, often at the expense of their health.